The Influence of Employee Engagement, Work Environment and Job Characteristics on Job Satisfaction and Performance - Wanda Gema Prasadio Akbar Hidayat (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study is to ascertain the relationship between job features, job satisfaction, and employee performance. This study employs an associative research type with a quantitative methodology. In this study, 115 people made up the sample, which was collected through saturation sampling. A questionnaire was used to collect the data, and the path analysis test was used to assess it. The findings indicated that employee work satisfaction is significantly influenced by employee involvement. The findings demonstrated that employee job satisfaction is significantly influenced by the workplace. Employee work happiness is significantly influenced by job features. Employee performance is significantly impacted by employee engagement. Employee performance is significantly impacted by the workplace. Job characteristics have a significant effect on employee performance. Job satisfaction has a significant effect on employee performance.